Detection of Chilling Injury Symptoms of Salak Pondoh Fruit during Cold Storage with Near Infrared Spectroscopy (NIRS) - Sutrisno Suro Mardjan; Jeri Indriyantoro (PERTETA, 2022)
One of the treatment methods that is suitable for maintaining the quality of salak pondoh fruit is cold storage. However, cold storage of salak pondoh fruit below its optimum storage temperature (15°C) can cause chilling injury/CI. This research aims to develop a non-destructive method of determining the CI symptoms of salak pondoh fruit during storage at 5°C with NIRS. Measurements were carried out for 14 days by measuring the CI parameters (pH and IL/ion leakage) and the NIR reflectance spectra. The best PLS method NIR calibration model for estimating pH was generated using the Savitzky-Golay Smoothing pretreatment with rk= 0.81, rv =0.76, SEC= 0.12%, SEP =0.12%, CV= 2.97%, RPD= 1.66, and consistency =100.06%. The IL slope of salak pondoh fruit correlated with the pH in a linear pattern relationship with the equation y = 0.1735x - 0.4305. The highest IL slope value was obtained on the 4th day of storage which means that IL has reached its peak, and CI was predicted to have occurred on the 4th day of storage.